ADAPTATION OF A PUSH NOTIFICATION TO OPTIMIZE HOME-BASED BUSINESS ORDERING SYSTEM - Muhammad Danial bin Mohd Amin; Zamlina binti Abdullah; Aishah Bte Ahmad @ Abdul Mutalib; Mazliana binti Hasnan; Azlin Dahlan (International Journal of Accounting, Finance and Business, 2022)
Home-based business has become a significant business trend in recent years. But there are also challenges. One challenge is the need to handle orders efficiently. There are owners who take orders manually. This poses difficulties to manage orders efficiently and it is prone to order errors. Thus, a new method is needed to assist home-based business owners managing orders better. This study proposed a mobile application that allows order taking with the adaptation of a push notification feature. The application was developed using the Modified Waterfall methodology and used the requirement gathering and analysis, design, implementation and testing phases only. The platform is Android Studio with Java as a language and connect to Firebase as database. Functional testing results showed that the functions worked correctly. Therefore, the mobile application shows potential to help the business owners to handle orders more systematically.